PENGARUH PENAMBAHAN TURBO CYCLONE AKSIAL TERHADAP ALIRAN DAN PERFORMA MOTOR BAKAR - Yusuf Rizal Fauzi (TURBO [Tulisan Riset Berbasis Online], 2018)
Complete combustion is a process that is expected in a burning, this can be achieved when a mixture of fuel and air evenly and fairly homogeneously distributed in the engine cylinder. This research aims to determine the effect of the flow and performance of the Honda GL PRO motorcycles with a cylinder capacity of 156 cc. This test is done to determine the effect of pre-combustion and post-combustion engine using turbo cyclone and the flow passing through the carburetor. This method uses fluent 6.2 software and statistical tests. With the use of axial turbo cyclone, it can improve the performance of gasoline engine with swirl flow obtaining fuel-air mixture better and get the desired performance. The results obtained from testing Effective Power by using turbo cyclone is 0.7239654 HP average, and 0.4151938 HP average without turbo cyclone. Torque by using turbo cyclone 0.2592512 kg.m average, and 0.1486808 kg.m average without turbo cyclone, the value of Effective Fuel Consumption by using turbo cyclone is 0.325596 kg/HP.hour average and 0.9273914 kg/HP.hour average without turbo cyclone. Efficiency Thermic Effective (ηe) by using turbo cyclone is 14.1434058 % average and 6.229145 % average without turbo cyclone.Keywords: Turbo cyclone, performance, and flow.